Retirement income redesigned : master plans for distribution : an adviser's guide for funding boomers' best years - Evensky, Harold; Katz, Deena B., 1950- (Bloomberg Financial., 2006)
"A how-to for financial advisers, offering practical suggestions and insights from a range of financial professionals on key issues relating to retirement income distribution planning."--Provided by publisher.